Improvement of the Thermal Performance of Air Collector by Using Inclined Baffles: A Three-Dimensional Analysis - Khaled Saad Alareby; Saleh Etaig; Nabil Elsharif (African Journal of Advanced Pure and Applied Sciences, 2024)
In response to the pressing global concerns surrounding energy consumption, particularly in the context of escalating global warming and climate change. This research is dedicated to enhancing the performance of solar air collectors. Employing advanced computational fluid dynamics (CFD) modeling, the study focuses on optimizing the design efficiency by scrutinizing the impact of varying inlet air velocities on crucial thermal parameters. The investigation utilizes ANSYS Fluent to simulate a 3-D collector, providing a comprehensive understanding of its physical dynamics and accurate solutions. Through a thorough analysis of different operating conditions, including overall thermal efficiency and total air pressure drop, the research aims to map the nuanced performance of the solar air collector. The outcomes highlight the 90° baffle angle as a standout performer, showcasing thermal efficiency exceeding 95%. However, this configuration is accompanied by the highest pressure drop among the considered designs. In contrast, the 60° baffle angle emerges as a well-balanced option, offering optimal overall pressure drop and an acceptable range of thermal efficiency. The interplay of these variables is further explored through detailed simulations, providing a holistic view of the collector’s behavior under various scenarios. This research not only contributes to the theoretical understanding of solar air collectors but also addresses practical considerations in design optimization. The findings underscore the importance of balancing thermal efficiency with operational considerations, guiding the selection of baffle angles for enhanced performance. As a result, this study not only advances the knowledge base in sustainable energy technologies but also provides actionable insights for the design and deployment of efficient solar air collectors.